Review of online breastfeeding information for Aboriginal and Torres Strait Islander women. Issue 4 (July 2021) - Hopkins, Mikaela; Meedya, Shahla; Ivers, Rowena; Charlton, Karen
Abstract: Background: Breastfeeding provides the healthiest start to life, but breastfeeding rates amongst Aboriginal and Torres Strait Islanders is lower than non-Indigenous women. Aim: To assess the accuracy, quality and appropriate presentation of online breastfeeding information for Aboriginal and Torres Strait Islander women in Australia. Methods: An online search conducted in Google, Bing and Yahoo search engines to identify any breastfeeding websites that provided information for Aboriginal and Torres Strait Islander women. Relevant websites were evaluated against: a) National Health and Medical Research Council clinical guidelines, b) the quality of health information on the Internet by using DISCERN instrument, and c) appropriate key design features for Aboriginal and Torres Strait Islander women. Results: The search located 348 sites with 31 being eligible for inclusion. Websites from governmental organizations had the highest accuracy while YouTube videos had the lowest accuracy. Three quarters (74%, n = 23) of sites incorporated the national clinical guidelines adequately, and most of the sites (77.8%, n = 24) were considered high quality. Only 23% (n = 7) of sites had sufficient key design features appropriate for Aboriginal and Torres Strait Islander women. Four websites were considered exemplary for their accuracy, quality and cultural appropriateness of information for Aboriginal and Torres Strait Islander women. Conclusion: Some websites are tailored to provide breastfeeding information and support to Aboriginal and Torres Strait Islander women. However, only a few contain culturally appropriate key design features. Further participatory action research is required to design online platforms for women from different cultural backgrounds that take into account cultural principles, beliefs and values.